Specific in vitro transcription of conalbumin gene is drastically decreased by single-point mutation in T-A-T-A box homology sequence. - Wasylyk, B (1980)
A single-point mutation, consisting of a T-to-G transversion, was made in the third nucleotide of the conalbumin gene T-A-T-A-A-A-A homology sequence (the T-A-T-A or Goldberg-Hogness box). In an in vitro system, specific transcription of the mutant DNA was drastically decreased compared to the normal gene. This down-mutation is consistent with the idea that the T-A-T-A box is an important element for specific initiation of transcription.